1979
DOI: 10.1093/bja/51.8.785
|View full text |Cite
|
Sign up to set email alerts
|

MORBIDITY IN GYNAECOLOGICAL DAY-CASE SURGERY: A comparison of two anaesthetic techniques

Abstract: The effectiveness of fentanyl, given as part of the anaesthetic technique, in reducing abdominal pain following outpatient gynaecological surgery has been examined. It was found to reduce significantly the frequency of abdominal pain in the period extending from discharge from hospital to the first evening, while not compromising surgical conditions nor increasing the frequency of other post-operative sequelae such as nausea and vomiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…None had any recall of the procedure. The incidence of emetic sequelae in this study was similar to that in a comparable series using fentanyl (Hunt et al 1979). This may reflect the known tendency of young women undergoing gynaecological operations to this complication and also the fact that more than half of them were given Syntocinon.…”
Section: Discussionsupporting
confidence: 86%
“…None had any recall of the procedure. The incidence of emetic sequelae in this study was similar to that in a comparable series using fentanyl (Hunt et al 1979). This may reflect the known tendency of young women undergoing gynaecological operations to this complication and also the fact that more than half of them were given Syntocinon.…”
Section: Discussionsupporting
confidence: 86%
“…Fahy and Marshall (1969) and Towey and others (1979) demonstrated a high frequency of postoperative symptoms after day-case surgery, some of which persist into the second day after operation. Hunt, Plantevin and Gilbert (1979) showed that a technique of anaesthesia using methohexitone and fentanyl reduced significantly the frequency of backache in the first few hours after operation, and of abdominal pain later on the day of operation, but had no effect on morbidity on the first and second days after operation, when compared with halothane. The present study confirmed a high morbidity rate after outpatient gynaecological surgery and showed that this was not influenced by the use of enflurane as opposed to halothane anaesthesia.…”
Section: Discussionmentioning
confidence: 98%
“…This was a pilot study run at two SWARM sites: University Hospital Plymouth NHS Trust, a large regional teaching hospital and tertiary referral centre; and Royal Cornwall Hospitals NHS trust, a busy district general hospital. We aimed to recruit approximately 50 patients between the two sites; this sample size was based on a previous similar study [2], group experience and guidelines for pilot study size [14].…”
Section: Methodsmentioning
confidence: 99%
“…The identification and measurement of outcomes from surgery and anaesthesia is an established priority for research in peri-operative medicine [1]. Progress and setbacks after discharge are monitored commonly by telephone calls, although these are labour intensive and contingent on the patient being contactable [2]. Further more, even daily inquiries lack granularity at a time when the patient's condition may be changing rapidly.…”
Section: Introductionmentioning
confidence: 99%